Conservation of the fishing resources of the Brazilian Atlantic Coast through the perspective of local ecological knowledge: a systematic review (2011 - 2021) (Research, Society and Development, 2021)
Artisanal fishermen are recognized as carriers of valuable knowledge about the resources they manage. Therefore, it is important that the experiences and knowledge developed by these populations be considered in the management of the environments they manage. The objective of this study was to understand how artisanal fishermen influence the conservation of fishery resources on the Brazilian Atlantic coast. For this, we reviewed articles that addressed fishing populations of Brazilian coastal regions and the conservation of these resources. This review demonstrated the need for studies that seek to understand this relationship, especially in the southern and northern regions of the country and that cover fisheries of other taxonomic groups besides bony fish. Most of the studies pointed out the potential of local ecological knowledge to contribute to the conservation of managed resources. Much of the knowledge held by fishermen is unknown by the scientific community and needs to be investigated and included in the management of the Brazilian coastal zone.